ANALISIS KUALITAS PELAYANAN DAN KOMPETENSI TENAGA KESEHATAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS TAJUR CITEUREUP - Erna Suarti (Journal of Innovation Research and Knowledge, 2025)
Service quality and competence are important to increase professionalism. For this reason, community health centers must focus more on developing competence and quality of service so that patients feel satisfied with the services provided by staff. Satisfaction is closely related to service users' assessment of the services they receive, because patient satisfaction is a good and bad illustration of the services provided by the health agency. This research is aimed at determining the influence of service quality and competence of health workers on patient satisfaction and its impact on interest in reusing services. This study used a cross sectional design, the population in this study were all patients who visited the Tajur Citeureup Community Health Center, with a sample size of 106 respondents. Samples were taken by Accidental Sampling. Data was collected using a questionnaire whose validity had been tested, the data was analyzed using path analysis. The statistical test results show that the variables that have a direct and simultaneous influence on patient satisfaction are the quality of health services and the competence of health workers with a contribution value of 0.319 or 31.9%. Suggestions for increasing competent health personnel through training on the quality of health services, so that all officers are able to provide quality services according to their competence.